PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS IV SD INPRES GERE - YOSEPHINA BELA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This research is motivated by the low results of evaluating student learning in science learning. Based on the results of evaluations on learning science in SD Inpres Gere, 20% (5 people) students reach KKM while 80% (20 people) of these students have not reached KKM. The KKM of science subjects is set at 75. Using the Process Skill Approach the researcher assumes that student learning outcomes can be improved while stimulating student interest in learning science. In the application of the Cycle I action, as many as 12 students (48%) achieved the KKM and in Cycle II all students completed (100%). With these results, the researchers found that the three domains of teacher assessment of students increased after the application of the Process Skill Approach.